2022
DOI: 10.3390/ani12121528
|View full text |Cite
|
Sign up to set email alerts
|

Fructooligosaccharide Supplementation Boosts Growth Performance, Antioxidant Status, and Cecal Microbiota Differently in Two Rabbit Breeds

Abstract: The present study examined the effects of fructooligosaccharide (FOS) supplementation in drinking water on the growth performance, carcass characteristics, hematological and biochemical parameters, antioxidant status, and cecal microbiota of New Zealand White (NZW) and APRI rabbits. A total of 180 male NZW and APRI rabbits (aged five weeks; average live body weight 700 ± 39 g) were divided into six groups (30 rabbits/group; 5 replicates/group) in a two × three factorial arrangement. Rabbits of each breed were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 38 publications
1
6
0
Order By: Relevance
“…Accordingly, using automated drinking devices, BV treatments commenced by providing 200 mL of BV‐infused drinking water to each cage. This approach aligns with methods employed by earlier researchers (Abd El‐Aziz, Abo Ghanima, et al, 2022; Pogány Simonová et al, 2022) who introduced additives into the drinking water of young rabbits using similar techniques. Following the provision of water with different BV concentrations (0.5, 1 and 2 mg/L), rabbits were allowed unrestricted access to untreated drinking water.…”
Section: Methodssupporting
confidence: 67%
See 2 more Smart Citations
“…Accordingly, using automated drinking devices, BV treatments commenced by providing 200 mL of BV‐infused drinking water to each cage. This approach aligns with methods employed by earlier researchers (Abd El‐Aziz, Abo Ghanima, et al, 2022; Pogány Simonová et al, 2022) who introduced additives into the drinking water of young rabbits using similar techniques. Following the provision of water with different BV concentrations (0.5, 1 and 2 mg/L), rabbits were allowed unrestricted access to untreated drinking water.…”
Section: Methodssupporting
confidence: 67%
“…These weights were subsequently subtracted from the initially provided quantities to determine the precise amount of feed consumed. The feed intake (FI), BW, body weight gain (BWG) and FCR were assessed according to the methodology outlined in a previous study by Abd El‐Aziz, Abo Ghanima et al (2022).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Dietary Zn supplementation was proven to benefit the growth performance of fattening rabbits under HS conditions [16,111,112]. Under HS conditions, the dietary inclusion of ZnO (100 mg/kg; [112]) or nano-Zn (20,40,60, and 80 mg/kg; [16]) improved BW, BWG, FI, and FCR in growing rabbits. Similarly, Kamel et al [111] observed that different dietary Zn sources (50 mg ZnO/kg diet or 30 mg nano-Zn/kg diet) enhanced the final BW, BWG, and FCR in growing rabbits who suffered from HS.…”
Section: Zincmentioning
confidence: 99%
“…Several dietary supplements-including vitamins, minerals, and enzymes-are already utilized to preserve the normal physiological status, support immunological responsiveness, and improve rabbit productivity in thermo-neutral and HS circumstances [14][15][16][17]. It has been suggested that probiotics, prebiotics, synbiotics, and organic acids could replace antibiotic growth enhancers in rabbit production because they promote a healthy intestinal environment [18][19][20][21]. Furthermore, phytobiotics or phytogenics are being utilized more frequently in rabbit nutrition as antioxidants, physiological stimulants, flavorings, digestive aids, and colorants, and for protecting and treating different pathological troubles [22][23][24].…”
Section: Introductionmentioning
confidence: 99%